Biomass allocation to vegetative and reproductive organs of Chenopodium acuminatum Willd. under soil nutrient and water stress - Huang, Yingxin; Zhao, Xueyong; Zhou, Daowei; Wang, Tianhui; Li, Guandi; Li, Qin (Bangladesh Journal of Botany, 2013)
Biomass allocation was size-dependent. Under soil nutrient, the plasticity of the leaf and reproductive allocation was true plasticity, the plasticity of stem allocation was apparent plasticity, which is dependent on plant size, but there was no plasticity in root allocation. Under soil water stress, the plasticity of root, leaf and reproductive allocation was true. In response to population density, the plasticity of stem allocation is true plasticity, while the value of the stem allocation is consistent because of the trade off between the effects of plant size and population density. The biomass allocation strategy increases reproductive allocation but decrease leaf allocation with the decrease of soil nutrient, when compared at the same plant size. At lower soil water, the plant allocated more biomass to the root and leaf rather than to reproductive organ. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15873 Bangladesh J. Bot. 42(1): 113-121, 2013 (June)